DIGITAL DATABASES AND UTILIZATION STRATEGIES (INTERNATIONAL CONFERENCE ON ANALYSIS OF MATHEMATICS AND EXACT SCIENCES, 2024)
The rapid evolution of digital technologies has profoundly impacted the way information is stored, accessed, and utilized. Digital databases are at the core of this transformation, providing efficient and scalable solutions for managing large volumes of data. This thesis examines the various strategies for utilizing digital databases effectively. It explores the types of digital databases, their advantages, and the challenges associated with their use. Additionally, it delves into best practices for database management, data retrieval, and security measures to ensure data integrity and accessibility.